Fahruddin Râzi’nin tefsiri Mefatihu’l Gayb’da Müşkilu’l Kur’an meselesi - Demirci, Sabri (My University, 2003)
Kur'an-ı Kerim'in ayetleri arasında ilk bakışta görülen çelişkileri, problematiği çözmekle ilgili bir bilim dalı olan Müşkilu'l- Kur'an meselesini Fahruddin Razi'nin tefsiri Mefatihu'l- Gayb baz alınarak incelenmiştir. Bir giriş ve iki bölümden oluşmaktadır. Girişte, Müşkilu'l-Kur'an kavramı ve onun yerine kullanılan kavramlar, müşkil kavramının menşei ve günümüze kadar müşkilu'l Kur'an ile ilgili eserler ve çalışmalar hakkında bilgi verilmiştir. Birinci bölümde, ayetleri anlamada ihtilaf sebebleri, çözüm yolları ve Kur'an'da ihtilaf olmayacağını bildiren ayetlerin tahlili yapılmıştır. İkinci bölümde müfessir Fahruddin Razi ve tefsirinden bahsedilir. Müşkilu'l- Kur'an ile ilgili konuların tahlili, şu anabaşlıklar altında yapılmıştır: Allah'ın zat ve sıfatlarında müşkil konuları,kevni ayetlerde, nübüvvetle, kıssalarla, ahiret halleriyle, mü'minlerin davranışlarıyla ilgili ayetlerdeki müşkil konuları ile dil ve ifadelerdeki çelişki konuları. Fahruddin Razi'nin tefsiri esas alınarak yapılan bu çalışmada diğer müfessirlerin yorumlarına da yer verilip, karşılaştırmalar yapılmıştır. Name and Surname: Sabri Demirci Field: Divinity Programme: Koranic Commentary - Tafsir Supervisor: Professor Suat Yıldırım Degree Awarded and Date : Doctorate - June 2003 The Question of the Difficulties of the Qur'an

THE QUESTION OF THE DIFFICULTIES OF THE QUR'AN ( MUSHKIL AL- QUR'AN ) IN FAHR AL- DIN AL- RAZI'S TAFSIR MEFATIH AL- GAYB This PhD. Thesis, which is called ''The Question of the Difficulties of the Qur'an (Mushkil al- Qur'an) in Fahr al- Din al- Razi's Tafsir Mefatih al- Gayb'' deals with the Question of Mushkil al- Qur'an which is the science of understanding and solving the so - called contradictions and problems found at first sight between the Qur'anic verses.The Study consists of three sections: In the first section we examined the term of ''Mushkil al Qur'an '' and the other related terms, the source of the words of mushkil al- Qur'an, the reasons for the disagreement on Qur'anic verses, the way of solutions and analysis of the verses on which Qur'an says that there can not be any dispute about them. In the second part we dealt with Mufassir (the commentator on the Qur'an) Fahr al- Din al-Razi and this Tafsir. We analysed the Mushkil al- Qur'an and related issues in Razi's Tafsir under the following main topics: Mushkil (the Difficult) subjects in verses related to God's essence and attributes, also mushkil subjects in verses related to the cosmos, prophethood, stories of the prophets, life after death, the actions of Muslims and the subjects related to language and expression. In this study which is based on Razi's Tafsir sometimes we made comparisons between Razi and other mufassirs (commentators).
Keywords: Tefsir